Dr. Hermann Gundert and Malayalam language - Sakkar̲iya, Skar̲iyā.; Frenz, Albrecht (Changanassery, Kerala, India : Centre for Kerala Studies, St. Berchmans' College : Kottayam : Distributors, Current Books, 1993)
On the contribution to Malayalam language of Hermann Gundert, a German missionary in Kerala; includes his biography.
"Dr. Hermann Gundert's works":p. 227-237
Includes bibliographical references and index.
Mode of access: Internet.
Keywords: Gundert, Hermann, -- 1814-1893.; Malayalam language